Sharia compliance service quality metrics for e-commerce: an exploratory analysis - Ribadu, Mohammed Bashir; Wan Ab. Rahman, Wan Nurhayati (School of Computing, UUM College of Arts and Sciences, 2017)
Despite the rising call for Sharia compliance in e-commerce systems, yet there are no established service quality metrics that would ensure Muslim consumer trust, use and users satisfaction. Therefore, we prudently proffered Sharia compliance service quality metrics for e-commerce that would foster e-commerce use, user satisfaction and net benefits for the over 1.8 billion Muslims globally. By deducing extant e-commerce service quality metrics from literature and harnessing the opinion of Sharia compliance scholars/experts, an integrative Sharia compliance service quality metrics for e-commerce are proffered. Fundamentally, Sharia compliance assurance of e-commerce systems is found to be an essential service quality metric that will ensure Muslim consumer trust, use, user satisfaction and net benefits from e-commerce. Whereas, conventional e-commerce service quality best practices that are aimed at enhancing the welfare and devoid of Sharia violations are also deemed important service quality metrics for Sharia compliance. Because, providing pre-sale, during the sale and post-sale support services are vital in ensuring the Sharia obligation of eliminating uncertainties, risk, losses, displeasure and discord emanating from e-commerce.